Pain, gain – mission. Issue 1 (1st January 2018) - Gossman, Peter; Powell, Stephen; Neame, Charles
Abstract: We present a short conceptual framework as an opinion piece for considering learning gain based on Biesta's three domains of educational purpose: qualification, socialisation and subjectification. We invite readers to reflect on the perspectives given in relation to different institutions mission statements around teaching and learning, and consider if the focus on developing methods for measuring learning gain is premature, given the lack of consensus regarding the nature of the learning to be measured.